Aceh, Qanun and National Law: Study on Legal Development Orientation - Nurdin, Ridwan; Ridwansyah, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
This study wants to examine the suitability of Aceh Qanun with National Law related to the Hierakicity of laws and regulations in Indonesia. In theory it is possible that the Aceh Government can build its own hierarchies that are not the same as the Central Government. This relates to the authority of the Aceh Qanun which is not the same as the Regional Regulation but the hierarchy that is built but meets the basic norms of the Indonesian constitution. There are two focuses which are the focus of this research. First, what is the character of the Aceh Qanun as a legal umbrella in the implementation of post-autonomy Aceh and post-peaceful Aceh? Second, What Is the Future of Law in Aceh? The results of the first research, the character of the Aceh Qanun as a legal umbrella in the implementation of post-autonomy Aceh and post-peaceful Aceh is expected to be able to build Aceh better because of the presence of Law Number 18 Year 2001 and Law Number 11 Year 2006 regarding new hopes for the people of Aceh itself specifically in the field of Islamic sharia. Second, the future of law in Aceh in the discussion of legal development, is greatly developing from creating new norms in Aceh Qanun Number 6 of 2014 concerning Jinayah Law, because regulating jinayah law in Aceh does not have to draw the Criminal Code or the Criminal Procedure Code.